Kris Aquino and the/as a Philippine horror genre - Sanchez, Louie Jon A. (2016)
Access online through this link: https://www.plarideljournal.org/article/kris-aquino-theas-philippine-horror-genre/

Translated article of "Si Kris Aquino at ang/bilang genre ng lagim sa Filipinas"
Keywords: Aquino, Kris; Horror films; Feng Shui (Film)